Performance of blue chip stocks in the Singapore stock market. - Kho, Daniel Gabriel. (2008)
This study serves to investigate whether Blue Chips stocks as a whole outperform the market in different situations. The motivation for the study comes at a time when the region is in the midst of an economic downturn and prudent investment with limited capital is crucial. The objective is to indicate to the investor whether the risk-adjusted performance of the Blue Chip indices is better than that of the market.